Reflexive judgement, risk and responses: HIV/Aids in Africa and Asia - Pick, David; Dayaram, Kandy (Sage, 2006)
Despite global acknowledgement of the Human Immunodeficiency Virus (HIV)/Acquired Deficiency Syndrome (Aids) reaching pandemic proportions with 37.8 million people (World Health Organisation, 2004) living with the infection, progress towards developing effective international responses to curb the spread of the disease has been slow. The focus of current debate tends to focus on the medical treatment and prevention of HIV/Aids, leading to emphasis being placed on the rapid increase in HIV infection as well as opportunistic diseases such as tuberculosis and malaria. The traditional view of responding to these challenges has been probing the high cost factors associated with antiretroviral treatment and burgeoning medical care needs. This paper argues that these responses are limited in their effect as they have a narrow, medical focus. This paper presents a broader perspective. It investigates the implications of HIV/Aids to the goals of national sustainable development using theoretical standpoints provided by reflexive modernization, namely the concepts of risk and reflexive judgement. Attention is given to those regions of the world - Africa and Asia where HIV/Aids are acute policy issues.